Strategic management : competitiveness and globalization concepts - Hitt, Michael A.; Hoskisson, Robert E.; Ireland, R. Duane (Cengage Learning, 2013)
Integrates the industrial organization model with a resource-based view of the firm to give you an understanding of how businesses use strategic management to establish a sustained competitive advantage. This book provides the understanding you need to apply strategic management tools and techniques for increased performance